PGD Synthase and PGD2 in Immune Resposne - Myungsoo Joo; Ruxana T. Sadikot (Hindawi Limited, 2012)
PGD2 is formed from arachidonic acid by successive enzyme reactions: oxygenation of arachidonic acid to PGH2, a common precursor of various prostanoids, catalyzed by cyclooxygenase, and isomerization of PGH2 to PGD2 by PGD synthases (PGDSs). PGD2 can be either pro- or anti-inflammatory depending on disease process and etiology. The anti-inflammatory and immunomodulatory attributes of PGDS/PGD2 provide opportunities for development of novel therapeutic approaches for resistant infections and refractory inflammatory diseases. This paper highlights the role of PGD synthases and PGD2 in immune inflammatory response.